2020
DOI: 10.3390/toxins12030159
|View full text |Cite
|
Sign up to set email alerts
|

Hypervolemia-Induced Immune Disturbances Do Not Involve IL-1ß but IL-6 and IL-10 Activation in Haemodialysis Patients

Abstract: Dysregulated fluid homeostasis is frequent in haemodialysis (HD) patients and is linked to inflammation which may be elicited by endotoxemia. The impact of hypervolemia on immune cells has not been studied in detail. Therefore, we analysed the hypervolemic activation of peripheral blood mononuclear cells (PBMCs) in HD with special focus on the NLRP3 inflammasome response. First, 45 HD were included in the observational study. Immune parameters including cell counts, caspase-1, oxidative stress, cytokine gene e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
2
5
0
Order By: Relevance
“…Most likely, this is at least partially caused by imbalanced anti-inflammatory mechanisms. The most prominent member of the anti-inflammatory arsenal is IL-10, and in line with the theoryinflammation is followed by anti-inflammation-we confirmed an earlier observation indicating higher IL-10 mRNA expression in hypervolemia [4].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Most likely, this is at least partially caused by imbalanced anti-inflammatory mechanisms. The most prominent member of the anti-inflammatory arsenal is IL-10, and in line with the theoryinflammation is followed by anti-inflammation-we confirmed an earlier observation indicating higher IL-10 mRNA expression in hypervolemia [4].…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, the inflammatory burden of hypervolemic chronic kidney disease patients is very high. Several authors reported higher IL-6 serum levels in overhydrated 2 of 14 dialysis patients [2][3][4]. Further, it is widely acknowledged that IL-6 is linked to cardiovascular diseases, in particular to chronic coronary syndrome [5], atherosclerosis [6], and hypertension [7] in chronic kidney disease.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that high levels of TNFα in COVID-19 could induce downstream activation of T H1 cells and block the final step of cT FH differentiation (Kaneko et al, 2020). This skewing may contribute to the delay observed in B cell responses to SARS-CoV-2 vaccination due to an insufficient feedback inhibition of pro-inflammatory cytokines (Perianayagam et al, 2002; Ulrich et al, 2020). The third dose was characterized in HD by the normalization of the effector function profile compared to the CI.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of hypervolemia and inflammation, both independent risk factors for mortality, can lead to a cumulative risk profile [85]. Ulrich et al [86] assessed the hypervolemic activation of peripheral blood mononuclear cells of HD patients with special emphasis on the NLRP3 inflammasome response. They found that the NLRP3 inflammasome is not activated by hypervolemia, suggesting that endotoxemia is not a main driver for inflammation in hypervolemic HD patients.…”
Section: Toll-like Receptors and Inflammasomesmentioning
confidence: 99%